Cosmetics Building, New York World's Fair 1939 (Grinnell Litho Co.)
Erected by the Fair Corporation, this building closely resembles a container for the products of the vast cosmetic industry which is portrayed in the numerous exhibits within its walls. Motion pictures, pageants and cosmetic shows daily fill the magnificent auditorium to capacity.